Introducing the Dutch Quality Registry for Acute Internal Medicine (DRAIM): Method of development and opportunities of use from a single-centre pilot study - Marleen G. A. M. van der Velde; Elisabeth M. Mols; Jelmer Alsma; Prabath W.B. Nanayakkara; Harm R. Haak; Marjolein N. T. Kremers (PLoS ONE, 2026)
Background The Dutch Quality Registry for Acute Internal Medicine (DRAIM) aims to evaluate and improve the quality of care for internal medicine patients presenting in the Dutch acute care chain. Using an online dashboard, comprising organizational, process, and patient characteristics, DRAIM provides insight into local institutional characteristics and enables comparisons with a benchmark. The aim is to identify potential bottlenecks, develop of interventions to optimize acute care and to create a learning environment. Methods DRAIM is a multicenter quality registry. However, this study reports findings from a single-centre pilot conducted in one teaching hospital. Data for this cohort was collected from November 2019 to June 2023, including patients presenting in the Emergency Department (ED) for internal medicine. Data was extracted from the Electronic Health Record, including patient and organizational characteristics, such as presenting complaint, and process- and outcome measures, such as length of stay in the ED (LOS-ED). Results A total of 6,071 patients aged ≥65 years were included. Older adults were more likely to experience adverse outcomes, including longer LOS-ED, increased hospital admissions, extended hospital stays, and higher in-hospital mortality rates. Additionally, 2.366 patients (46.6%) presented with general malaise. Compared to patients with other presenting complaints, those with general malaise had longer LOS-ED and higher hospital admission rates. These findings prompted the development and implementation of a standardized care-pathway for patients with non-specific complaints in the ED. Conclusion This single-centre pilot demonstrates the potential of DRAIM to provide valuable insights into acute-care processes and identify bottlenecks in patient flow. While findings cannot yet be generalised nationally, they highlight important trends, such as the vulnerability of older patients and those presenting with non-specific complaints. Future use of DRAIM for multicentre studies will validate these observations and facilitate the evaluation and improvement of the Dutch acute-care network.